Analisis Pengaruh U-Turn Terhadap Kinerja Ruas Jalan Letjen Hertasning Kota Makassar Dan Ruas Jalan Tun Abdul Razak Kabupaten Gowa - Bama Rusmali; Abd. Rahim Nurdin; Tamrin Mallawangeng (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
The median opening on Jalan Letjen Hertasing and Jalan Tun Abdul Razak for the U-Turn movement, often results in traffic jams. This study was conducted to determine the characteristics of traffic flow and U-Turn performance on these roads. This research is expected to be a reference to the Makassar City government and the Gowa Regency government in taking a policy on these roads. The methodology used in this study uses MKJI 1997. Based on the calculation of the performance of the segment in its current condition, Letjen Hertasning road has the highest degree of saturation value of 0.89 so it is categorized as being included in the E road service level at 17.00 – 18.00 WITA and causes queue lengths. up to 280 meters. For the Tun Abdul Razak road, the highest degree of saturation is 1.17, so it is categorized into the F road service level at 17.00 – 18.00 WITA and causes the queue length to reach 784 meters.